Prototype Pintu Air Berbasis Android dan Mikrokontroller Menggunakan Bluetooth - Muhammad Irmansyah; Junaldi junaldi; Arya Bima Surya (Teknik Elektro Politeknik Negeri Padang, 2018)
Generally, in existing dams facilitated by sluice are used to control the amount of water on that dam. This sluice is controlled by a human that has a duty to maintain the stability of the water on that dams or not to be more than existing limitation. Therefore the doorman clerk must be ready at all times and it is impossible for him to do it over time. The water gate drain human energy when open and then close it again. This tool is using as a replacement for human power. By the statement improved advanced technology development taht combines Android with Bluetooth-based Atmega 328 microcontroller instruments. This remote sluice control works automatically. The Ping sensor measures the level of the water and sluice, after that the recorded data will be processed by microcontroller and send it into the Android through Bluetooth. Besides that, the Android data that consist of water level and sluice will be captured on the LCD screen. On the other hand, the Beeb voice that getting from a buzzer will active when the level of the water sign exceeds 3 cm. In this research, Android is used as a monitoring tool and control system remotely. Furthermore, this tool also uses a DC motor in order to open and close sluice, so it makes the water gate capable to be closed and opened based on expected distance. This system hopefully can automatically open the water gate if the water level higher than a limit position by using an android control system based on operator expectation. That way there is no human power needed to open the water gate. In other words, effectiveness and efficiency will occur.